A comparative theoretical study on the impact of social media marketing on consumer preferences by gender (Architecture Image Studies, 2026)
This comparative theoretical study examines the impact of social media on consumer preferences, with a focus on consumer gender. The study aims to understand the prevailing perception that consumer gender both influences and is influenced by promotional messages on social media.The study employs a descriptive-analytical approach to determine the extent to which consumer gender influences their consumer preferences and to identify the methods used by popular social media platforms (Facebook, Instagram, TikTok, and WhatsApp) to promote products using gender-based promotional messages.Based on statistics and public opinion polls, the study reveals that promotional messages on social media platforms like Facebook and Instagram continue to target consumers based on their gender, among other factors.The study demonstrates that significant differences still influence promotional messages published on social media. Therefore, the study recommends considering gender, along with other factors, when distributing promotional messages to ultimately achieve organizational goals.